Government Intervention Through Collaborative Approach in Promoting The Adoption of Green Procurement for Construction Projects - Asmah Alia Mohamad Bohari,; Bidin, Zafikha Aida; Khalil , Natasha (International Journal of Sustainable Construction Engineering and Technology, 2022)
The green procurement (GP) for construction industry and its implementation requires government intervention particularly through policies, initiatives, and incentives. GP is relatively a new concept especially in Malaysian construction industry and its implementation is still ambiguous even though GP is globally recognised. Hesitation in implementing GP among construction stakeholder is due to lacking of familiarity, lack of available standard guidelines and awareness among stakeholders. These are the challenges that hindered the adoption of GP among construction stakeholders in Malaysia. In construction industry, collaboration among construction stakeholder is fundamental towards construction projects’ success and also depending on the support from various stakeholders to meet the project objectives . Thus, this conceptual paper is intended to highlight the importance of collaborative approach and  way forward with GP as a strategy to solve environmental problems. Specifically, it looks into government’s intervention to promote, empower the understanding, creating awareness, and willingness of construction stakeholders to implement GP in construction projects.  The preliminary framework is developed through literature review and questionnaire survey were used as the method to collect and analyze the findings. The paper concludes that collaborative approach provide a better platform for all the parties, particularly the construction stakeholders to be better engaged, in terms of communication, well informed, more aware and willing to implement the GP throughout the construction process.